Implementasi Program Pemberantasan Peredaran Gelap Narkotika MelaluiI Jalur Perbatasan Negara Republik Indonesia Di Kalimantan Barat - Bhayu Kuncoro (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2020)
AbstractThis research entitled The Implentation of the Narcotics Dark Circulation Eradication Program Through the Republic of Indonesias Border Line in West Kalimantan analyzed based on the theory put forward by Merilee S. Grindle. This research is a type of descriptive research with a qualitative approach. The type of data in this study is primary data obtained from interviews with informants and secondary data obtained from various official documents related to research.The implementation of the Narcotics Dark Circulatioan Eradication Prgoram through the Republic of Indonesias Border Line in West Kalimantan has not been able to run optimally due to several factors, namely: 1. The esistence of interests that influence the parties affected by the program, 2. The strategy of the disadvantaged actors especially those involved in narcotics illicit traffincking, 3. Limited resources, 4. Top-down decision making locations.Based on these problems, the author can make suggestions, namely: 1. There needs to be a support program in the form of a border surveillance program, 2. Increasing the capacity of program implementors both in quality and quantity, 3. Focusing on eradication programs and other support programs in border areas. Key words : The Implementation Policy, Narcotics Eradication.